Pengaruh Marketing Mix terhadap Keputusan Wisatawan Mancanegara mengunjungi Ekowisata Mangrove di Tahura Ngurah Rai, Denpasar - Gusti Ayu Dwi Kurnia; Gde Indra Bhaskara (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Marketing is one of the important strategies in tourism activities. With the marketing, tourists know the tourist attraction that will be visited. Marketing consists of several aspects, such as product, place/distributions, price and promotion (marketing mix). This research was conducted to determine the form of marketing mix at Tahura Ngurah Rai Mangrove Ecotourism and measure how much influence the marketing mix had on the decisions of foreign tourists visiting Tahura Ngurah Rai Ecotourism. The method used in research is quantitative method. Data collection is conducted by questionnaire, observation, and literature study. While the data analysis technique used is the Important Performance Analysis (IPA) technique. The results of study showed that the components of the marketing mix consisting of products, prices, places / distributions, and promotions still did not meet the level of tourists satisfaction, There were still several components that had to be increased such as price and place. Therefore, the manager must focus on to the component that doesn’t meet the level of tourist satisfaction since it can influence the tourist visiting decisions. Keywords : Marketing Mix, Ecotourism, Tahura Ngurah Rai